Computer analysis of images and patterns : 18th international conference, CAIP 2019, Salerno, Italy, September 3-5, 2019 : proceedings.: 18th international conference, CAIP 2019, Salerno, Italy, September 3-5, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available